Living between brackets: Public-private patriarchal violence and the mental state of women on both sides of Radcliffe line - Mostafizur Rahman; Nahida Anwar (Universitas Negeri Yogyakarta, 2022)
The study examines the public-private patriarchal notion of Sylvia Walby and its violent effects on women’s mental state during and after the partition of Indian Subcontinent. Systematic electronic searches were conducted in 7 electronic databases and 42 studies were included for final review. Findings explored private patriarchal violence including ‘honor killing’, ‘collective suicide’, hate and curse, social rejection, sex trap, cancelled communality, and twice displacement. Public patriarchal violence became evident through rape, forced marriage, and abduction. The private and public patriarchal violence captivated and imprisoned women’s minds and resulted in mental traumas including estrangement and emotional detachment, unbalanced minds, diseased thought and paranoia, post-traumatic stress disorder, ‘feeling of loss’, depression and sadism, ‘disturbing memory’ and insanity, haunted nightmare and spooky dream, and concealed grief.